Análise da força de trabalho em saúde bucal no Estado do Maranhão - DUARTE, Karlinne Maria Martins (2022)
The oral health workforce is formed by the oral health team, consisting of the dental surgeon (CD), Oral Health Technician (TSB) and Oral Health Assistant (ASB). The aim of this study was to analyze the oral health workforce at the Maranhão state, contextualizing economic, social and geographical indicators. It is a hybrid, cross-sectional study with analysis of individual primary data, with data collection carried out through questionnaires and an ecological type, whose unit of analysis was the city, with secondary data from institutional sites. The first article resulting from the study showed that the training of TSB promoted by PROFAPS through ETSUS-MA in 17 cities had a high level of satisfaction in relation to the skills common to SUS professionals and specific to the TSB, but specific skills for prevention and support clinical and dental care aimed at restoring health were evaluated in an unsatisfactory way and could be better developed. It was also possible to verify the high turnover of workers, reflecting the precariousness of the employment bond and the discontinuity of the human resources policy, evidencing the low valuation of the trained professional. The second study demonstrates the spread of dentists (DC) across the Maranhão state. Except for the Açailândia health region, the others are in accordance with the parameters of the Health Ministry of offering 1 dentist for up to 4000 inhabitants. The distribution of dentists who provide services to SUS and those who do not serve SUS is not uniform among the cities and is directly correlated to population size, PIB per capita and IDH-M impacting the quality of oral health care. Thus, we conclude that the distribution of the oral health workforce at the Maranhão state, suffers from the low appreciation of the human capital. This fact needs to be accompanied by managers in the three spheres of government and by the professional associations that represent these professional categories.